Freedom to trade shares in companies contributing to the Algerian legislation - KHELFAOUI, Abdelbaki (Journal of Human Sciences, 2020)
Joint stock companies constitute the optimal legal and economic framework for investing in modern economies, so that they carry out large commercial and industrial projects, taking into account the capital and savings of individuals and institutions that they can collect. , and perhaps most helped by the ability of their shares to be traded by trading methods which It meets the requirements of commercial life, which is expressed in the principle of free trading of shares in public limited companies, c that is to say the capacity of the shareholder to freely transfer his shares without the complications imposed by civil law, and without this affecting the status of the company and its survival and the continuity of its activity. And the importance of this principle becomes clear in the light of the activity of the financial markets and the stock market based on speculation on stocks, which have become an economic and financial activity by which the strength of the economy of all country is measured, which made the adoption of the principle of freedom of negotiation of the shares and the support a need to respond to it The Algerian legislator, eager to create an atmosphere conducive to savings and investment.